The media and public agenda among the Malay and Chinese communities during the 2008 Malaysian General Elections - Syed Abdullah Idid, Syed Arabi; Chang, Peng Kee (Canadian Center of Science and Education, 2012)
Media are said to set the public agenda. However, the actual scenario of a public agenda among the Malay and Chinese communities in Malaysia has yet to be ascertained. This study employs both content analysis and survey to examine media and public agenda of two major ethnic groups during the 2008 General Elections. In total, 9,135 news items, relating to elections, were obtained from three major languange newspapers, comprising Utusan Malaysia, Berita Harian, Sin Chew Daily, Nanyang Siang Pau, The Star, and New Straits Times, during the campaign period. There were 12 important issues identified. Overall, the study found media agenda had no significant rank-order correlation with the public agenda, or the important issues raised by 1,454 Malay, Chinese, and Indian respondents nationwide. The same happens to the Malay media agenda with Malay public agenda. The study found the Chinese media agenda to have a significant rank-order correlation with the Chinese public agenda suggesting the newspapers influence among the Chinese readers on what to think about. Ethnic newspapers therefore could be setting the agenda for the various ethnic groups during elections.